TINJAUAN PERHITUNGAN DAN PELAPORAN PAJAK PERTAMBAHAN NILAI (PPN) BERBASIS ELEKTRONIK ATAS PENJUALAN POPOK GENKI MOKO MOKO PADA PT OJI INDO MAKMUR PERKASA (INDOFOOD GROUP) - Amalia Novita Sulistyani, (2020)
VAT is an indirect tax that occurs if there is an activity, event, or act that causes tax payable, for example the delivery of goods or services where the tax is imposed on other people or third parties so that it has a role in increasing state revenue. The author implements Field Work Practices (PKL) at PT Oji Indo Makmur Perkasa the company is a manufacturing company engaged in the production and sale of diapers. The purpose of this thesis report is made to find out how to make an output tax invoice for the sale of diaper genki moko-moko and to find out filling and report electronic periodic tax returns with e-invoicing application, to know the calculation, deposit, and reporting of electronic-based VAT using e-billing when depositing VAT and using online tax when reporting VAT, in addition to knowing the input tax invoice obtained and scanning documents on scanbarcode where at the end of the month the calculation of input tax is obtained with the collected output tax which will then be deposited or compensated. The results of the fieldwork can be concluded that PT Oji Indo Makmur Perkasa uses an electronic system in calculating, depositing and reporting VAT has been carried out in accordance with general provisions in force.